Peran Transportasi Online di Masa Pandemi: Studi Kasus Gojek Di Medan - Sumitro Sarkum; Abd. Rasyid Syamsuri (Institut Transportasi dan Logistik Trisakti, 2021)
On June 1, 2020, the Indonesian government implemented a new standard in the midst of the COVID-19 pandemic. Despite the fact that large-scale social restrictions are in place, Medan City permits online motorcycle taxi drivers to carry people. Additionally, the epidemiological factors that have contributed to the drop in the number of positive cases are less than 50%. This study uses Gojek Medan in the New Normal Covid-19 to investigate how consumers decide which online transportation services to use depending on price, trust, and advertising. Users that have transacted through the Gojek application make up the study's demographic, and the sample size of 52 respondents represents this population. Utilizing quantitative data analysis is the study methodology. Part of the study's findings indicate that the factors Price, Trust, and Promotion have a favorable and significant impact on Medan's Gojek Online Consumer Decisions. Price, Trust, and Promotion can all be used to explain consumer decisions, according to a value of 61.3 percent found by assessing the coefficient of determination adjusted for adjusted R square. While other characteristics that were not looked at in this study can account for the remaining 38.7%, which could serve as a research topic for future studies